The Effect of Budget Efficiency Policies on the Quality and Sustainability of Islamic Education in Indonesia: Challenges and Strategic Responses - Vita Fitriatul Ulya; Ahmad Suyanto; Masdar Hilmy; Ah. Zakki Fuad (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
The purpose of this study is to investigate the impact of government budget efficiency measures on the quality of Islamic education in Indonesia. As Islamic education plays a crucial role in the national education system—serving millions of students across Islamic boarding schools (pesantren) and madrasas—budgetary policies are likely to have significant consequences for educational outcomes, teacher welfare, infrastructure, and institutional sustainability. This research employs a qualitative literature review methodology, drawing on secondary sources such as scholarly publications, policy reports, recent academic articles, and digital media content, including YouTube and other social platforms. A descriptive analytical approach is utilized to assess the extent to which budget efficiency policies influence the quality of Islamic educational institutions. The findings indicate that budget reductions adversely affect teacher professional development initiatives, availability of educational facilities, and the overall welfare of teachers. Furthermore, diminished financial support has led to reduced access to essential educational resources for students in madrasas and pesantren. To address these challenges, the study recommends the implementation of alternative strategies, including strengthened governance mechanisms, increased collaboration with the private sector, and more transparent, targeted budget management practices. The study concludes with a call for further empirical research to deepen understanding of the long-term implications of budget efficiency measures on Islamic education in Indonesia.